Studying the Built Environment - Temple, Marion, ....- (London : Red Globe Press, 2004)
This unique book introduces students to the themes and aspects of studying the built environment. Contemporary issues such as sustainability and urbanization preface the explanation of the core subject disciplines of architecture, construction management, planning, real estate management and surveying. The distinctive student experience of learning about the built environment is explored with a focus upon learning and teaching methods, learning skills and assessment. The final chapter of the book looks at the links between academic study and professional practice.
Keywords: Built environment